224k views
2 votes
If u(x) =x5 -x4+x2 and v(x) =-x 2 which expression is equivalent to (u/v) (x)

2 Answers

3 votes

Answer:c

Step-by-step explanation:

—x^3+x^2-1

User Aflatoon Singh
by
5.6k points
0 votes
For this case we have the following functions:

u (x) = x ^ 5 -x ^ 4 + x ^ 2 v (x) = -x ^ 2
Dividing the functions we have:

(u / v) (x) = (u(x))/(v(x))
Substituting we have:

(u / v) (x) = (x^5 -x^4 + x^2)/(-x^2)
Rewriting we have:

(u / v) (x) = (-x^5 + x^4 - x^2)/(x^2)

(u / v) (x) = (-x^5)/(x^2) + (x^4)/(x^2) + (- x^2)/(x^2) (u / v) (x) = -x^3 + x^2 - 1
Answer:
An expression that is equivalent to (u/v) (x) is:

(u / v) (x) = -x^3 + x^2 - 1

User Joseph Wu
by
5.5k points